Study on Mechanical Properties of Shale Under Different Loading Rates - Wei, Yuanlong; Zhao, Lingyun; Yuan, Tao; Liu, Wei (Frontiers in Earth Science, 2022)
In the process of shale gas development, different drilling, hydro-fracturing, and pumping speeds will produce different productivity effects. This reflects the effect of the loading rate of rock mechanics. Therefore, it is of great scientific significance to study the deformation and failure characteristics of shale under different loading rates. In order to reveal the loading rate effect of the Longmaxi shale, a series of laboratory experiments were carried out, including scanning electron microscope, XRD, and uniaxial compression tests at different loading rates. The results show that 1) the peak strength and elastic modulus of shale increase with the increase in the loading rate, but Poisson’s ratio has no obvious rule with the increase in the loading rate. In contrast, the loading rate causes the peak strength to vary by about 20%, which is larger than that of the elastic modulus. 2) The loading rate has a significant influence on shale failure. A higher loading rate will lead to severe damage but with simple cracks, whereas a lower loading rate will lead to complex damage of cracks. With the decrease in the strain rate, the length of the failure crack increases greatly. Therefore, a lower strain rate is helpful to form more broken fragments in the shale matrix. 3) By analyzing the relationship between elastic strain energy/dissipated energy and the loading rate, it is found that the elastic strain rate has a preliminary increasing and then a decreasing trend with the loading rate, but the dissipated energy has a decreasing trend with the loading rate. A higher loading rate is helpful to increase the brittleness of the shale, but a lower loading rate is beneficial to forming more cracks and a greater degree of fracture in the shale matrix. The effect of the loading rate on the mechanical properties and fracture properties of the shale is discussed. It is suggested that the lower hydro-fracturing rate is useful for generating more complex crack networks in the shale reservoirs.